ACTIVATION OF THE ROLE OF UINSU 125 KKN STUDENTS IN IMPROVING EDUCATION AND HEALTH IN SIBOLANGIT VILLAGE - Anggraini Srg, Dini; Nurfebia, Karina; Pratama, Dimas; Mughiroh, Hafizul; Jumiaty, Ety (LPPM Univ. Ibn Khaldun Bogor, 2023)
Sibolangit Village is one of the tourist villages in North Sumatra, this village is located in the Deli Serdang Regency, North Sumatra Province. Limited education in terms of accessing the latest learning information makes it quite difficult for several schools in Sibolangit Village. The health of the elderly is also a special concern there. The method of implementing Real Work Lecture (KKN) activities for North Sumatra State Islamic University students to the community consists of JBT (Additional Learning Hours), JBM (Night Study Hours), JBP (Companion Study Hours), Quran Learning, elderly health, and stunting counseling. All programs carried out have run well which can be seen from the enthusiasm of students in following all the programs that have been made. In following all the programs that have been made the same is the case with the elderly who regularly participate in gymnastics activities and mothers and children who participate in posyandu and counseling.